Analysis Of Environmental Effects On Adolescent Dating Patterns In The Pare Sub-District, Kediri Regency - Wulandari, Ratna Feti; Wardhani, Ratih Kusuma; Dinastiti, Vide Bahtera (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study examined environmental effects that impact on dating patterns of adolescent. Unhealthy dating patterns indicate adolescent sexual behavior when they were dating. The impact of sexual behavior is unwanted pregnancies and early marriages, thereby increasing the risk of infection during labor and even death and childbirth defects. This study aims to analyze the influence of environment on adolescent dating patterns. This research design used cross sectional method and the sample was collected on 300 respondents using the snowball sampling technique. Data was analyzed using the Rank Spearmen Correlation test. The results showed that most of the respondents were in a sufficient environment (71.0%) and their dating patterns were mostly in the healthy dating pattern category (97%). The results of statistical testing showed that there was an environmental influence on the dating patterns of adolescents with a correlation coefficient of -0.128 (p <0.05) with a significance level of 0.026.